(untitled) (Journal of Economic Additions, 2026)
This research paper highlights the importance of financial and accounting disclosure in improving institutional performance. The performance of a national company specialized in the manufacturing of agricultural equipment was evaluated through the analysis of its revenues, costs, and financial indicators. The results showed that the implementation of disclosure practices led to an improvement in both financial and administrative performance, along with a noticeable increase in financial independence. The study recommends taking effective measures such as employee training and enhancing transparency to support sound disclosure. These findings can be used to support decision-making and improve performance in similar institutions. Jel Classification Codes: M41, M48, G38.